Serine synthesis through PHGDH coordinates nucleotide levels by maintaining central carbon metabolism. Issue 1 (December 2018) - Reid, Michael; Allen, Annamarie; Liu, Shiyu; Liberti, Maria; Liu, Pei; Liu, Xiaojing; Dai, Ziwei; Gao, Xia; Wang, Qian; Liu, Ying; Lai, Luhua; Locasale, Jason
Abstract Phosphoglycerate dehydrogenase (PHGDH) catalyzes the committed step in de novo serine biosynthesis. Paradoxically, PHGDH and serine synthesis are required in the presence of abundant environmental serine even when serine uptake exceeds the requirements for nucleotide synthesis. Here, we establish a mechanism for how PHGDH maintains nucleotide metabolism. We show that inhibition of PHGDH induces alterations in nucleotide metabolism independent of serine utilization. These changes are not attributable to defects in serine-derived nucleotide synthesis and redox maintenance, another key aspect of serine metabolism, but result from disruption of mass balance within central carbon metabolism. Mechanistically, this leads to simultaneous alterations in both the pentose phosphate pathway and the tri-carboxylic acid cycle, as we demonstrate based on a quantitative model. These findings define a mechanism whereby disruption of one metabolic pathway induces toxicity by simultaneously affecting the activity of multiple related pathways. Serine synthesis from glucose is required even when serine is available from the environment. Here, the authors explain this paradox by showing that the enzyme PHGDH enables nucleotide synthesis by coordinating anabolic fluxes related to central carbon metabolism, independent of its role in serine production.